On Optimality of Pursuit Time - Ibragimov, Gafurjan I. (Institute for Mathematical Research, 2008)
We study a differential game described by an infinite system of differential equations with integral constraints on controls of players. This system is obtained by a parabolic equation by using decomposition method. We obtained an equation to find the optimal pursuit time and examined the series representing the left hand side of the equation. Moreover necessary and sufficient condition for convergence of the series is obtained.